Loop Quantum Cosmological Model From ADM Hamiltonian - Ding, You; Zhang, Xiangdong (Frontiers in Astronomy and Space Sciences, 2022)
The loop quantum cosmological model from ADM Hamiltonian is studied in this paper. We consider the spatially flat homogeneous FRW model. It turns out that the modified Friedmann equation keeps the same form as the APS LQC model. However, the critical matter density for the bounce point is only a quarter of the previous APS model, i.e. $ρ_{cL}=\frac{ρ_c}{4}$. This is interesting because the lower critical bounce density means the quantum gravity effects will get involved earlier than the previous LQC model. Besides, the lower critical density also means the detection of quantum gravity effects easier than the previous model.